Successful use of ultrasound elastography in the preliminary intermediate evaluation of therapeutic response in patients with Hodgkin’s lymphoma - E. V. Kovaleva; T. Yu. Danzanova; G. T. Sinyukova; E. A. Gudilina; P. I. Lepedatu; G. F. Allahverdieva; P. A. Zeynalova; A. A. Semenova; F. M. Abbasbeyli (Онкогематология, 2019)
Objective. The possibilities of ultrasound elastography of the lymph nodes as an additional technique for the intermediate control of treatment of patients with Hodgkin’s lymphoma are determined.Materials and methods. A prospective study included patients with a diagnosis of classical Hodgkin’s lymphoma with affected superficial lymph nodes. Patients underwent ultrasound elastography (compression elastography and shear wave elastography) of the enlarged lymph nodes before treatment and after two cycles of chemotherapy. The reasons for the ultrasound examination of superficial lymph nodes after the second chemotherapy cycle were: an earlier ultrasound examination with revealed changes in the superficial lymph nodes (in 100% of cases), preservation of the palpable formation in the projection of the superficial lymph nodes (in 56.9% of cases). Before ultrasound elastography of the studied group of patients, the positive dynamics after two cycles of chemotherapy was confirmed by PET/CT (Deauville scale 2—3).Results and conclusion. According to strain elastography, stiff heterogeneous (third type of elastogram) and stiff structure (fourth type of elastogram) of affected lymph nodes were noted in 53.5 and 42.3% of cases, respectively, before treatment. After two cycles of chemotherapy, these types of elastogram were 52.1 and 43.7% of cases, respectively. According to the results of shear wave elastography before and after treatment, a decrease in the average shear wave velocity in the affected lymph nodes from 2.67 + 0.69 to 2.21 + 0.40m/s (p = 0.000003) was revealed.